Evaluating Accessibility and Comfort of Pedestrian Skybridges: An Observational and Physiological Approach - Putri Chandra Pratiwi; Bambang Suhardi; Widyo Laksono (Asian Journal of Social and Humanities, 2026)
This study evaluates the accessibility and psychological comfort of users on the skybridge connecting Tirtonadi Terminal and Solo Balapan Station. The research was conducted to assess the suitability of the facility to the needs of vulnerable groups, particularly people with disabilities and the elderly, who are often overlooked in pedestrian infrastructure design. A mixed-methods approach was applied through field observations, interviews with 10 users, and physiological stress measurements using Galvanic Skin Response (GSR). The analysis results showed an average accessibility index value of 1.28 (categorized as less accessible), with several critical aspects such as ramps, signs, ventilation, and lighting not meeting standards. Furthermore, GSR data revealed an average increase in stress of 25%, with 90% of respondents experiencing anxiety or distress when crossing the skybridge. These findings confirm that limited physical facilities directly impact users' psychological comfort. This study recommends the implementation of inclusive design based on PUPR standards, improvements to supporting facilities, and the integration of stress monitoring technology as part of the development of sustainable pedestrian infrastructure.